Jewish country houses and country house studies - Cox, O (Taylor and Francis, 2019)
The Jewish country houses explored in this issue represent a group of properties spread across Europe that have hitherto escaped systematic research by country house studies. In thinking about what was distinctively Jewish about the country houses of the Jewish elite this issue consolidates three significant trends in country house studies – the house, collections and wider estate as a dynamic entity shaped by a range of historical processes; the global interconnectedness of country houses; the importance of collaborative projects spanning the heritage sector and academic – and poses exciting new questions that may be profitably adapted by country house studies to advance scholarly understanding of non-Jewish houses.